The Relationship between Higher Education and Women Empowerment in Pakistan - Naz, Arab; Ashraf, Faiza (UMT Education Review, 2020)
Women empowerment is one of the critical dimensions of a feminist perspective. In patriarchal societies, women are oppressed and suppressed; hence higher education is considered a remedy to equip them to deal with issues arising from undue oppression and suppression. This study aimed to find the relationship between the attainment of higher education among women and women empowerment. The study has been carried out in Central Punjab, Pakistan. The study was framed under a correlational research design. Data was collected from a sample of 200 respondents equally selected (50 from each) of four different universities, including the University of Gujrat, University of Management and Technology, Lahore, University of Minhaj, University of Lahore. A stratified random sampling technique has been utilized, whereby 200 samples were questioned through a structured questionnaire. The collected information was analyzed by using both descriptive and inferential statistics. Findings showed a strong correlation between the attainment of higher education and women empowerment. The correlation was determined among one independent variable (attainment of higher education) and four dependent variables, including the power of decision making, increased political participation, economic independence, respect, and self-esteem.All variables have been found significantly associated with each other, which provides evidence that higher education attainment leads to women empowerment. Based on the findings of the study, it is concluded that higher education plays a significant role in liberating women from oppression and suppression.